A group of genes required for maintenance of the amnioserosa tissue in Drosophila. - Frank, L.H.; Rushlow, C. (Development, 1996)
The amnioserosa is an extraembryonic, epithelial tissue that covers the dorsal side of the Drosophila embryo. The initial development of the amnioserosa is controlled by the dorsoventral patterning genes. Here we show that a group of genes, which we refer to as the U-shaped-group (ush-group), is required for maintenance of the amnioserosa tissue once it has differentiated. Using several molecular markers, we examined amnioserosa development in the ush-group mutants: u-shaped (ush), hindsight (hnt), serpent (srp) and tail-up (tup). Our results show that the amnioserosa in these mutants is specified correctly and begins to differentiate as in wild type. However, following germ-band extension, there is a premature loss of the amnioserosa. We demonstrate that this cell loss is a consequence of programmed cell death (apoptosis) in ush, hnt and srp, but not in tup. We discuss the role of the ush-group genes in maintaining the amnioserosa's viability. We also discuss a possible role for the amnioserosa in germ-band retraction in light of these mutants' unretracted phenotype.